Unintentional childhood injury patterns, odds, and outcomes in Kampala City: an analysis of surveillance data from the National Pediatric Emergency Unit - Mutto, Milton; Lawoko, Stephen; Nansamba, Catherine; Ovuga, Emilio; Svanstrom, Leif (Journal of injury and violence research, 2011)
Unintentional Childhood Injuries pose a major public health challenge in Africa and Uganda. Previous estimates of the problem may have underestimated the childhood problem. We set to determine unintentional childhood injury pattern, odds, and outcomes at the National Paediatric Emergency unit in Kampala city using surveillance data. Methods: Incident proportions, odds and proportional rates were calculated and used to determine unintentional injury patterns across childhood (1-12 years). Results: A total of 556 cases recorded between January and May 2008 were analyzed: majority had been transported to hospital by mothers using mini-buses, private cars, and motorcycles. Median distance from injury location to hospital was 5 km. Homes, roads, and schools were leading injury locations. Males constituted 60% of the cases. Play and daily living activities were commonest injury time activities. Falls, burns and traffic accounted for 70.5% of unintentional childhood injuries. Burns, open wounds, fractures were commonest injury types. Motorcycles, buses and passenger-cars caused most crashes. Play grounds, furniture, stairs and trees were commonest source of falls. Most burn injuries were caused by liquids, fires and hot objects. 43.8% of cases were admitted. 30% were discharged without disability; 10%, were disabled; 1%, died. Injury odds and proportional incidence rates varied with age, place and cause. Poisoning and drowning were rare. Local pediatric injury priorities should include home, road and school safety. Conclusions: Unintentional injuries are common causes of hospital visit by children under 13 years especially boys. Homes, roads and educational facilities are commonest unintentional injury sites. Significant age and gender differences exist in intentional injury causation, characteristics and outcomes. In its current form, our surveillance system seems inefficient in capturing poisoning and drowning. The local prevention priorities could include home, road and school safety; especially dissemination and uptake of proven interventions. Burns should be focus of domestic injury prevention among under-fives. Commercial passenger motorcycles require better regulation and control.
Keywords: Unintentional- Childhood; Injuries; Emergency Unit; Referral Hospital